Uniform and Non-Uniform Pumping Effect on Ce:Nd:YAG Side-Pumped Solar Laser Output Performance - Vistas, Cláudia R. (2022)
Funding: This research was funded by Science and Technology Foundation of Portuguese Ministry of Science, Technology and Higher Education and the exploratory research project EXPL/FIS-OTI/0332/2021. This research was also funded by the Solar Facilities for European Research Area—Third Phase (SFERA III), Grant Agreement No. 823802. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.